Inoperative Education as Drift between Eastern and Western Philosophies - Tyson Edward Lewis (MDPI AG, 2024)
"Inoperative Education as Drift Between Eastern and Western Philosophies" expands upon recent notions of "inoperativity" in educational philosophy in the West through an encounter with the Taoist philosophy of Zhuangzi. Thus far, the concept of inoperativity has largely been inspired by Giorgio Agamben, the contemporary Italian critical theorist. Educational theory has taken up inoperativity in order to rethink the school as a space of free time, the student as a studier, and the gymnastic body, to name only a few. Through a comparative, philosophical analysis, inoperativity is rethought in a decisively Taoist register in order to generate three movements of inoperativity: drift as use, drift as use of uselessness, and drift as deactivation of learning (un-learning).